Risco de irregularidade contábil em processos licitatórios nos municípios do estado de Goiás: análise da percepção dos profissionais da contabilidade integrantes das comissões de licitações - Santos, Joney Belo dos (2025)
This dissertation analyzed the impact of the professional training of members of municipal bidding committees in the state of Goiás on the perceived risk of irregularities in the evaluation of financial reports during the economic-financial qualification process. The study involved 37 public officials from 26 municipalities, with data collection conducted via electronic questionnaire between October and December 2024. The data were analyzed using Stata software, using descriptive and association data analysis methods. The results indicate that most public officials who evaluate the QEF are commissioned employees with varied higher education degrees, most with postgraduate degrees. Accounting degrees stood out as a factor that increases the perception of irregularity risks, highlighting the importance of specific training in this context. However, only a minority of the officials have a degree in Accounting, which limits in-depth analysis. Although education, age, and longer public service experience provide a better perception of risks, with the exception of having a "postgraduate degree," no positive relationship or association was identified between the observed variables. Aspects such as work status, educational institution, and time on the committee did not significantly influence the results. The study highlights the importance of public managers considering the profile of bidding committee members to improve the assessment of the economic and financial qualifications of bidding companies, contributing to efficient public management. Limitations such as the data collection period and the election period were highlighted. Future research is suggested to expand and compare these findings.